2010
DOI: 10.1038/npp.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate Desynchronization and Functional Connectivity with the Amygdala During a Working Memory Task Predict Rapid Antidepressant Response to Ketamine

Abstract: Pregenual anterior cingulate (pgACC) hyperactivity differentiates treatment responders from non-responders to various pharmacological antidepressant interventions, including ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist. Evidence of pgACC hyperactivition during non-emotional working memory tasks in patients with major depressive disorder (MDD) highlights the importance of this region for processing both emotionally-salient and cognitive stimuli. However, it is unclear whether pgACC activity migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
149
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(164 citation statements)
references
References 42 publications
12
149
1
2
Order By: Relevance
“…This would also correspond to the time when ketamine increases levels of glutamate [47], which could underlie the increased activity observed in the FST. As pointed out by the authors [46], rapamycin would not be expected to block the effects of ketamine at this time point since the induction of synaptic proteins and synaptogenesis is delayed by approximately 2 h. This later time point corresponds more closely to the initial antidepressant response observed in depressed patients [36,40].…”
Section: Role Of Mammalian Target Of Rapamycin Signalling In the Actimentioning
confidence: 91%
See 1 more Smart Citation
“…This would also correspond to the time when ketamine increases levels of glutamate [47], which could underlie the increased activity observed in the FST. As pointed out by the authors [46], rapamycin would not be expected to block the effects of ketamine at this time point since the induction of synaptic proteins and synaptogenesis is delayed by approximately 2 h. This later time point corresponds more closely to the initial antidepressant response observed in depressed patients [36,40].…”
Section: Role Of Mammalian Target Of Rapamycin Signalling In the Actimentioning
confidence: 91%
“…This is critical as mTOR is expressed in neuronal and glial cell bodies, which could mask changes in the smaller dendritic compartment. Second, the behavioural analysis was conducted 30 min after ketamine administration, when ketamine levels are still high in brain and corresponds to the time when patients experience mild psychotomimetic and dissociative effects of ketamine [36,40]. This would also correspond to the time when ketamine increases levels of glutamate [47], which could underlie the increased activity observed in the FST.…”
Section: Role Of Mammalian Target Of Rapamycin Signalling In the Actimentioning
confidence: 99%
“…It has been suggested that the psychotropic effects of ketamine might also be related to alterations in the connectivity between specific brain regions, which has been demonstrated both in animal (Bolton et al, 2012) and in human studies (Salvadore et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Information processing by these circuits following such a provocative load can then be quantified using various imaging (Fineberg et al, 2010;Stahl, 2008;Bush et al, 2005) or electrophysiological techniques (Salvadore et al, 2009(Salvadore et al, , 2010. The N-back cognitive load, for example, is a 'stress test' generally used to tax the functioning of the dorsolateral prefrontal cortex (DLPFC); the Stroop task tests the function of the dorsal anterior cingulate cortex; facial expressions test the amygdala and perigenual anterior cingulate cortex (pgACC); gambling tasks test the orbital frontal cortex; and so on (Salvadore et al, 2009(Salvadore et al, , 2010Fineberg et al, 2010;Stahl, 2008;Bush et al, 2005). The reaction of a brain circuit to the specific load placed upon it can be used as a measure of the efficiency of information processing in that brain circuit.…”
Section: What Is Psychiatric Stress Testing?mentioning
confidence: 99%
“…The study of Salvadore et al (2010) provides a glimpse into how such 'psychiatric stress tests' may also translate into predictors of who will respond to a specific drug.…”
mentioning
confidence: 99%